Macroeconomic Analysis of Expenditures on Education as Human Capital Investments - T. Kiss, Judit (International Journal of Engineering and Management Sciences, 2017)
The importance of actions on adaptation to economic change associated with the knowledge-based economy has continuously grown both regional and national level. Individuals’ flexibly adjust and the knowledge acquired in all forms of education is very important factors in the evolving knowledge-based economies. We examine the fiscal and private expenditures on education among OECD countries between 2005 and 2013, and we analyse the development of education expenditures with particular attention to Hungary.